The Forward Chaining Method for Determining Abnormalities in Newborns - Yuniarti , Pipi; Pebriani, Emi (Sekolah Tinggi Ilmu Kesehatan Sapta Bakti, 2025)
Abnormalities in newborns are usually congenital. These congenital abnormalities are abnormalities that occur in the baby's structural development from the time the baby begins life from conception. These congenital abnormalities are usually the cause of abortion, stillbirth, or death soon after birth. Infant deaths in the first month of life are often caused by severe congenital abnormalities. The purpose of this study is to help parents quickly identify the types of abnormalities in newborns without having to wait in line for a specialist. This study used the Forward Chaining method. The Forward Chaining method is an inference technique in an expert system that works from facts or symptoms to a final conclusion. In this study, the Forward Chaining method was used to determine the types of abnormalities in newborns. Not all babies born are normal, even if they appear normal. Each abnormality in a newborn baby is accompanied by specific symptoms. To determine the type of abnormality that occurs in newborns, this is done by paying attention to the symptoms experienced by the baby so that the public can obtain information about the abnormality, and for doctors this application can be used as an assistant as well as a reference to provide information to the public about the types of abnormalities in newborns. For this reason, an expert system is designed that uses Forward Chaining to help people who want to consult about their babies to find out if there are any abnormalities in their babies.